2003
DOI: 10.1023/b:ejep.0000020447.59150.f9
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for cardiovascular mortality in psoriasis inpatients but not in outpatients

Abstract: We have conducted a historical cohort study to assess cardiovascular mortality among psoriasis patients. Using the Swedish Inpatient Registry, we selected 8991 patients hospitalized for psoriasis at dermatological wards. To represent an outpatient cohort, 19,757 members of the Swedish Psoriasis Association were selected. Mortality from cardiovascular diseases was compared with the general population. We found no increased cardiovascular mortality among outpatients with psoriasis (standardized mortality ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
319
3
25

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(370 citation statements)
references
References 23 publications
16
319
3
25
Order By: Relevance
“…However, these studies have focused on highly selected psoriasis patients, such as those hospitalized for their disease or with multiple comorbidities, including diabetes mellitus, obesity, hypertension and smoking. 5,6,[15][16][17][18][19] These studies describe findings of manifest atherosclerosis, but give limited information on early, subclinical changes in psoriasis (patients Data are mean ± SD. Table 3 Multiple linear regression analyses factors associated with carotid artery IMT, FMD and NTD in the entire group of the 86 study subjects Kimhi et al also found that patients with psoriatic arthritis had greater IMT than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have focused on highly selected psoriasis patients, such as those hospitalized for their disease or with multiple comorbidities, including diabetes mellitus, obesity, hypertension and smoking. 5,6,[15][16][17][18][19] These studies describe findings of manifest atherosclerosis, but give limited information on early, subclinical changes in psoriasis (patients Data are mean ± SD. Table 3 Multiple linear regression analyses factors associated with carotid artery IMT, FMD and NTD in the entire group of the 86 study subjects Kimhi et al also found that patients with psoriatic arthritis had greater IMT than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Mallbris et al 83 2004 Using the Swedish Inpatient Registry, there appeared to be no increased cardiovascular mortality among outpatients with psoriasis. Overall risk among inpatients admitted at least once was increased by 50%.…”
Section: Ofmentioning
confidence: 96%
“…81 They found no increase in CVD mortality. Severe psoriasis, defined by use of systemic medications, 82 hospitalization at an early age, or repeated hospitalization, 83 has been shown by two high quality cohort studies to increase the risk of death. These patients with severe disease have increased mortality, which persisted after adjustment for DM, HTN, BMI, and smoking and after exclusion of patients with inflammatory arthropathy.…”
Section: Impact Of Psoriasis On Cvd and Total Mortalitymentioning
confidence: 99%
“…5,6 In initial assessments the increased risk of myocardial infarction and vaso-occlusive disease was attributed to the increased prevalence of risk factors. These risk factors have been attributed to behaviors such as obesity and smoking which are thought to be provoked by the psychosocial burden of the disease.…”
Section: General Cardiovascular Riskmentioning
confidence: 99%